SYNTHESIS, CHARACTERIZATION AND ANTIOXIDANT ACTIVITY OF 7-HYDROXY-3',4'-DIMETHOXYFLAVONE - Elfi Susanti VH; Sabirin Matsjeh; Tutik Dwi Wahyuningsih; Mustofa Mustofa; Tri Redjeki (Indonesian Journal of Chemistry, 2012)
Synthesis of flavones and their derivatives has attracted considerable attention due to their significant pharmaceutical effects. 7-hydroxy-3',4'-dimethoxyflavone has been synthesized and its antioxidant activity has been investigated. Flavone was synthesized by oxidative cyclization of chalcone. 2',4'-dihydroxy-3,4-dimethoxychalcone was prepared by Claisen-Schmidt condensation of 2,4-dihydroxyacetophenones with 3,4-dimethoxybenzaldehydes in the presence of aqueous solution of sodium hydroxide and ethanol at room temperature. Oxidative cyclization of 2',4'-dihydroxy-3,4-dimethoxychalcone was done by using I2 catalyst in DMSO to form 7-hydroxy-3',4'-dimethoxyflavone. The synthesized compounds were characterized by means of their UV-Vis, IR, 1H-NMR and 13C-NMR spectral data. The compound was tested for their antioxidant activities by DPPH method.